Susceptibility of kale cultivars to the wheat bug, Nysius huttoni (Hemiptera: Lygaeidae) in New Zealand. Issue 3 (2nd July 2020) - Tiwari, Sundar; Saville, David J.; Wratten, Stephen D.
ABSTRACT: Seedlings of kale cultivars in New Zealand are highly susceptible to direct feeding by the wheat bug Nysius huttoni (Hemiptera: Lygaeidae), an endemic insect pest. Two assays (choice and no-choice) were conducted to compare the relative susceptibility of seedlings of the six most popular kale cultivars in New Zealand (Kestrel, Gruner, Sovereign, Regal, Corka and Coleor). The earliest occurrence of feeding damage in the choice assay was on cv. Kestrel, significantly earlier than on Corka and Gruner. In the no-choice assay, significantly more wheat bugs were found on Kestrel than on Corka. Damage to Kestrel occurred significantly earlier than on all the other cultivars except Corka. Reduction in plant dry weight was significantly higher on Coleor and Kestrel. These results are important for developing integrated pest management protocols for kale pests.